2020
DOI: 10.1177/1535370220958011
|View full text |Cite
|
Sign up to set email alerts
|

Role of age and neuroinflammation in the mechanism of cognitive deficits in sickle cell disease

Abstract: This study aims to determine whether sickle cell mice could recapitulate features of cognitive and neurobehavioral impairment observed in sickle cell patients and whether neuroinflammation could be a potential therapeutic target as in other non-sickle cell disease-related cognitive dysfunction. Cognitive (learning and memory) and behavioral (anxiety) deficits in 13- and later 6-month-old male Townes humanized sickle cell (SS) and matched control (AA) mice were evaluated using novel object recognition (NOR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 89 publications
2
16
0
1
Order By: Relevance
“…[47][48][49] Abnormalities of sphingolipids metabolism, especially increased acid sphingomyelinase, have been shown to play a role in age-related neuroinflammation and neurodegenerative changes. 50,51 Recent studies in animal models of SCD have also shown that presence of cognitive impairment in 6 months 52 and in 13 months 53 old mice have cellular evidence of neuroinflammation and neurodegeneration as observed in aged non-sickle cell mice (described earlier). Taken together, neurological injuries associated with SCD at a relatively young age suggest accelerated cerebrovascular aging.…”
Section: Increased Risk Of Neurological Injuries and Cognitive Abnorm...mentioning
confidence: 74%
“…[47][48][49] Abnormalities of sphingolipids metabolism, especially increased acid sphingomyelinase, have been shown to play a role in age-related neuroinflammation and neurodegenerative changes. 50,51 Recent studies in animal models of SCD have also shown that presence of cognitive impairment in 6 months 52 and in 13 months 53 old mice have cellular evidence of neuroinflammation and neurodegeneration as observed in aged non-sickle cell mice (described earlier). Taken together, neurological injuries associated with SCD at a relatively young age suggest accelerated cerebrovascular aging.…”
Section: Increased Risk Of Neurological Injuries and Cognitive Abnorm...mentioning
confidence: 74%
“…107 In addition, Hardy et al . 15 observed increased microglial activation, decreased dendrite arbors and dendritic spine density (markers of structural neuroplasticity), increased proportion of immature dendritic spines (a marker of functional neuroplasticity), and increased density of peripherally derived CD45 + mononuclear cells in the hippocampus of aged Townes humanized SCA mice; all of these pathological changes correlated with poor cognitive function compared to younger SCA and healthy control mice. Both the behavioral changes and histological changes were abrogated by treatment with minocycline, a tetracycline antibiotic with antineuroinflammatory activities that effectively crosses the blood–brain barrier.…”
Section: Neuroinflammationmentioning
confidence: 89%
“…In addition, treated SCD mice had significant improvements on learning and memory tasks compared to untreated mice; the treated mice scored no differently than age and sex-matched controls. 15 The largest human trial to date, the Minocycline in Alzheimer Disease Efficacy (MADE) Trial, evaluated the role of minocycline at two dosing strategies to slow the rate of cognitive decline in individuals with mild Alzheimer’s disease over 24 months of follow-up; although no statistically significant difference was observed when comparing the patients treated at either minocycline dose versus placebo, a trend toward a significantly lower rate of decline was seen when comparing the higher-dose versus low-dose minocycline therapy. 142 In addition, the study used the standardized Mini-Mental State Examination (MMSE) as their cognitive outcome measure; however, the MMSE has very limited ability to diagnose mild cognitive impairment and does not actually examine executive function.…”
Section: Therapiesmentioning
confidence: 99%
“…A recent report demonstrated cognitive deficit in a sickle cell disease mouse model. 19 Patients with chronic pulmonary disease are at higher risk of developing dementia including patients with chronic obstructive pulmonary disease. 20,21 Additionally, vascular abnormalities in this group of patients are not limited to the lung and include multi-system vascular deficiencies in other organs including brain, kidney, and heart which complicate the course and outcomes of the disease in these patients.…”
Section: Examples Of National Heart Lung and Blood Institute -Funded ...mentioning
confidence: 99%